Determination of Minimum Number of Frustule for Identification of Diatoms in Telaga Cebong, Dieng, Central Java, Indonesia - Oki Rachmalia Rozi; Tri Retnaningsih Soeprobowati; Riche Hariyati (Indonesian Journal of Limnology, 2022)
Diatoms belong to the division of Bacillariophyta; their cell walls composition of silica (SiO2) was the primary characteristic of their structure. Diatoms are good for water quality assessment and paleolimnological analysis. The determination number of frustule which has to be counted for diatom is one of the critical steps in process identification. Several studies usually use a range starting from 100-600 frustules, which refers to the "fixed count" method, that is time-consuming. Research about the minimum frustules number that is acceptable for water character in Indonesia has been limited studied. This research aim is to determine the minimum number of frustules need to identify the diatom assemblage, especially at Telaga Cebong, Dieng, Central Java, Indonesia. The sediment samples were taken vertically with D’Section corer until a depth of 200 cm sediment samples then  sliced every 10 cm. The labwork activites consisted of  digestion, preparation, enumeration, and identification of diatom species with the numberof frustules of 100,200, 300, 400, 500, and 600. The diatom data are analyzed with the formula for the maximum efficiency value. Based on 19 sediment samples from different sediment layers, the maximum efficiency value obtained was above the range of 0.85 to 0.92. The number of identified species remained stable after a minimum of 300 frustules. Therefore, at least 300 frustules are needed for identification of diatom for paleoreconstructions at Cebong Lake.